Bioactive Compound Analysis Of An Ayurveda Oil, Gandharvahastadi Eranda Tailam - Queen Z, Edal; Prabhu K, Prabhu K; Mohammed, Hasan; CS, Janaki; Jones, Sumathi; Balakrishnan, Deepalakkshmi; Chauhan, Shivakshi (Journal of Neonatal Surgery, 2025)
The present study investigates the therapeutic potential of Gandharvahastadi Eranda Tailam, a traditional Ayurvedic formulation, known for promoting regular bowel movements and acting as a hepatic stimulant. Using Gas Chromatography-Mass Spectrometry (GC-MS), the study identifies several key bioactive compounds present in the formulation, including Chloroacetic acid tetradecyl ester, 4-t-Butyl-2-(1-methyl-2-nitroethyl) cyclohexanone, Chloroacetic acid pentadecyl ester, 1,2-Benzenedicarboxylic acid bis(2-methylpropyl) ester, 7-Methyl-Z-tetradecen-1-ol acetate, Ricinoleic acid, Stigmasterol, and γ-Sitosterol. These compounds are known for their anti-inflammatory, antioxidant, and hepatoprotective properties, which contribute to the therapeutic efficacy of the formulation. Despite their recognized benefits, the specific roles of each molecule in the overall health benefits of Gandharvahastadi Eranda Tailam remain to be elucidated. The findings of this study offer valuable insights into the chemical composition of this Ayurvedic medicine, paving the way for further research to explore the precise mechanisms by which these bioactive components exert their therapeutic effects. By understanding the bioactive profile, this research aims to contribute to the scientific validation of traditional Ayurvedic formulations for modern healthcare applications.